Jurist in context : a memoir / William Twining. - Twining, William, 1934- (Law in context., 2019)
This is the engaging and accessible intellectual memoir of a leading jurist. It tells the story of the development of his thoughts and writings over sixty years in the context of three continents and addresses the complexities of decolonisation, the troubles in Belfast, the contextual turn in legal studies, rethinking evidence and the implications of globalisation which have been central to his life and research. In propounding his original views as an enthusiastic self-styled 'legal nationalist', Twining maps his ideas of law as a unique discipline, which pervades all spheres of social and political life while combining theory and practice, concepts and values, facts and rules in uniquely fascinating ways. Addressed to academic lawyers generally and to other non-specialists, this story brings out the importance and fascinations of a discipline that has changed, expanded and diversified in the post-War years, with an eye to its future development and potential.